Pole piece and preparation method thereof, battery and power utilization device

By setting a conductive buffer layer in the electrode sheet and using carbon material, the problems of edge collapse and winding and breaking of the active layer during cold pressing are solved, and the structural stability of the electrode sheet and the cycling performance of the battery are improved.

CN119208528AActive Publication Date: 2024-12-27CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310752271.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-25
Publication Date
2024-12-27
Estimated Expiration
2043-06-25

AI Technical Summary

Technical Problem

During the cold pressing process of the battery, the edge collapse and winding and broken belt of the electrode sheet are serious problems, which affects the battery performance.

Method used

A conductive buffer layer is provided between the current collector and the active layer of the electrode sheet, and carbon materials such as graphite, soft carbon, and sole olefins are contained in the conductive buffer layer and the active layer. The structural characteristics of these materials cause slippage under pressure , slow down the extrusion effect of active materials on the current collector, reduce the ductility difference, and improve the edge collapse and belt breakage problems.

Benefits of technology

It effectively reduces the energy density loss of the pole sheet, improves structural stability and cyclic stability, reduces the extension and damage of the current collector, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208528A_ABST
    Figure CN119208528A_ABST
Patent Text Reader

Abstract

The invention relates to the field of batteries, in particular to a pole piece and a preparation method thereof, a battery and a power utilization device. The pole piece comprises a current collector, a conductive buffer layer and an active layer which are sequentially stacked, at least one of the conductive buffer layer and the active layer comprises a carbon material, and the carbon material comprises one or more of graphite, soft carbon and football alkene. The pole piece can slow down the extrusion effect of the active material in the active layer on the current collector and reduce the extension of the current collector, so that the extension difference between the current collector and the active layer is reduced, and the problems of edge collapse of the active layer and belt breakage due to winding are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a pole piece and a preparation method thereof, a battery and an electrical device. Background Art

[0002] During the battery chemical reaction process, electron transfer is usually achieved by using active materials in the pole piece. The active materials in the pole piece are usually combined on one or both surfaces of the current collector. A common method of combining the active material with the current collector is to make an electrode active slurry with the active material and an adhesive, a conductive agent, etc., and then coat the electrode active slurry on one or both surfaces of the current collector. After drying and cold pressing, an active layer including active materials can be formed on the surface of the current collector. After cold pressing, the pole piece can be further processed by winding or other processes.

[0003] In actual production, the active layer often collapses during the cold pressing process, which leads to breakage problems in the winding process (winding tape breakage), seriously reducing the quality of the electrode and thus affecting battery performance. Summary of the invention

[0004] In view of the above problems, the present application provides a pole piece and a preparation method thereof, a battery and an electrical device, which can alleviate the problems of active layer edge collapse and winding breakage of the pole piece during processing.

[0005] In a first aspect, the present application provides a pole piece, which includes a current collector, a conductive buffer layer and an active layer stacked in sequence, wherein at least one of the conductive buffer layer and the active layer contains a carbon material, and the carbon material includes one or more of graphite, soft carbon, and ethylene.

[0006] In the technical solution of the embodiment of the present application, a conductive buffer layer is arranged between the current collector and the active layer, and carbon materials such as graphite, soft carbon, and footballene are arranged in at least one of the conductive buffer layer and the active layer. These carbon materials have special structures and properties, and can undergo internal structural slip and / or inter-particle slip under pressure.

[0007] Specifically, in the crystal of graphite, carbon is arranged in an orderly and anisotropic manner, with carbon atoms in the same layer arranged in sp 2Hybridization forms covalent bonds, and each carbon atom is connected to three other atoms by three covalent bonds. The layers are mainly connected by molecular bonds, and the molecular attraction between the layers is weak. Therefore, graphite has the characteristics of soft particles, weak van der Waals force interaction between particles, and relative slippage between the layers during cold pressing. Similar to graphite, spherical carbon also has a layered structure, with molecular bonds between the layers, and weak molecular attraction between the layers. Relative slippage between the layers occurs during cold pressing. Soft carbon refers to amorphous carbon materials that can be graphitized at high temperatures above 2500°C, that is, amorphous carbon that is easily graphitized at high temperatures. The microcrystalline structure of soft carbon has lattice stripes, which are parallel straight stripes. At the same time, there is a large amount of amorphous carbon in the structure, and the crystal structure is relatively loose and disordered, and the layers are easy to slip during cold pressing.

[0008] Therefore, when the conductive buffer layer contains carbon material, the squeezing effect of the active material in the active layer on the current collector can be slowed down, the extension of the current collector can be reduced, and the extension difference between the current collector and the active layer can be reduced, and the problem of edge collapse of the active layer and the problem of winding broken tape can be improved. When the active layer contains carbon material, under the joint action of the conductive buffer layer and the carbon material, the squeezing effect of the active material in the active layer on the current collector can also be slowed down, and the problem of edge collapse of the active layer and the problem of winding broken tape can be finally improved.

[0009] At the same time, since the conductive buffer layer has a partitioning effect on the active layer and the current collector, the active material in the active layer does not directly contact the current collector, which can improve the damage of the active material to the current collector during the cold pressing process.

[0010] In some embodiments, the Dv50 of the carbon material is 0.4-1.5 μm, optionally 0.7-0.9 μm.

[0011] In some embodiments, the carbon material has a Dv90 of 1 to 4 μm, optionally 1 to 3 μm.

[0012] The carbon material used in the embodiment of the present application has a smaller particle size, which is conducive to forming an extremely thin conductive buffer layer. Since the carbon material generally has a lower energy density than the active material in the active layer, when the conductive buffer layer contains the carbon material, the thinner the thickness of the conductive buffer layer is, the more conducive it is to reducing the energy density loss of the pole piece. Alternatively, the carbon material has a smaller particle size, which enables it to have good dispersibility in the active layer.

[0013] In some embodiments, the conductive buffer layer comprises the carbon material, and the mass content of the carbon material in the conductive buffer layer is greater than or equal to 5% and less than 100%, and optionally 14% to 56%. Under appropriate dosage, the structural characteristics of the carbon material can be fully utilized to improve the problem of active layer edge collapse and winding belt breakage caused by large current collector extension, and reduce the damage to the current collector; and it is beneficial to reduce the energy density loss of the pole piece.

[0014] In some embodiments, the active layer includes the carbon material, and the mass content of the carbon material in the active layer is 1% to 5%, and optionally 3% to 5%. In the case where the active layer includes the carbon material, considering that these carbon materials generally have a lower energy density than the active material in the active layer, therefore, controlling the content of the carbon material in the active layer within a suitable range is conducive to reducing the energy density loss of the pole piece.

[0015] In some embodiments, the thickness of the conductive buffer layer is 3 to 6 μm; optionally, 3 to 4 μm. Since carbon materials generally have lower energy density than active materials in the active layer, when the conductive buffer layer contains carbon materials, the conductive buffer layer has an extremely thin thickness, which is beneficial to reduce the energy density loss of the pole piece (under a fixed pole piece compaction density and thickness, the smaller the thickness of the conductive buffer layer, the greater the thickness of the active layer, the more active materials in the active layer, and the greater the energy density of the pole piece).

[0016] In a second aspect, the present application provides a method for preparing a pole piece, comprising the steps of: preparing a conductive buffer layer on the surface of a current collector; preparing an active layer on the surface of the conductive buffer layer; wherein at least one of the conductive buffer layer and the active layer comprises a carbon material, and the carbon material comprises one or more of graphite, soft carbon, and ethylene.

[0017] In the embodiment of the present application, a conductive buffer layer and an active layer are sequentially prepared on the surface of a current collector to obtain a pole piece including a current collector, a conductive buffer layer and an active layer stacked in sequence, and the preparation method is simple.

[0018] In some embodiments, the step of preparing the conductive buffer layer includes: providing a primer slurry, and coating the primer slurry on the surface of the current collector.

[0019] In some embodiments, the viscosity of the primer slurry is 100-1000 mPa / s (25° C.), optionally 300-600 mPa / s. Appropriate slurry viscosity is helpful for the processing and manufacturing of the conductive buffer layer.

[0020] In a third aspect, the present application provides a battery, which includes the above-mentioned electrode piece, or includes the electrode piece prepared by the above-mentioned method.

[0021] The pole piece of the embodiment of the present application can reduce the extension of the current collector under the action of the carbon material and the conductive buffer layer, improve the problem of active layer edge collapse and winding belt breakage, and the current collector is less damaged, so the pole piece has good structural stability. After the pole piece of the embodiment of the present application is applied to the battery, it will be beneficial to improve the cycle stability of the battery.

[0022] In a fourth aspect, the present application provides an electrical device, wherein the electrical device comprises the above-mentioned battery.

[0023] The battery disclosed in the embodiments of the present application can be used to provide electrical energy to various electrical devices.

[0024] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0026] Figure 1 Schematic diagram of the structure of the current collector and the active layer in a traditional pole piece (left figure) and the schematic diagram of the pole piece structure of an embodiment of the present application (right figure);

[0027] Figure 2 is a schematic diagram of a battery module according to an embodiment of the present application;

[0028] Figure 3 A schematic diagram of a battery pack according to an embodiment of the present application;

[0029] Figure 4 for Figure 3 An exploded view of a battery pack according to an embodiment of the present application is shown;

[0030] Figure 5 A schematic diagram of a battery according to an embodiment of the present application;

[0031] Figure 6 for Figure 5 An exploded view of a battery according to an embodiment of the present application is shown;

[0032] Figure 7 A schematic diagram of an electrical device using a battery as a power source according to an embodiment of the present application.

[0033] Reference numerals:

[0034] 1-battery pack; 2-upper box; 3-lower box; 4-battery module; 5-battery cell; 51-housing; 52-electrode assembly; 53-cover plate. DETAILED DESCRIPTION

[0035] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0037] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0038] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0039] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0040] In the description of the embodiments of the present application, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0041] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0042] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0043] Conventional pole pieces usually include a current collector and an active layer disposed on one or both surfaces of the current collector, such as Figure 1 As shown in the left figure. In the battery chemical reaction process, the active materials in the active layer of the pole piece are usually used to realize the transfer of electrons and ions. The common method of combining the active layer with the current collector is to make the active material with an adhesive, a conductive agent, etc. into an electrode active slurry, and then coat the electrode active slurry on one or both surfaces of the current collector. After drying and cold pressing, an active layer including active materials can be formed on the surface of the current collector. After cold pressing, the pole piece can be further processed by winding or other processes.

[0044] The structure of more active materials in the active layer will not slide under pressure, so during the cold pressing process, the active materials squeeze each other and exert a certain pressure on the current collector. Commonly used current collectors include metal current collectors, such as aluminum foil, copper foil, etc. Although these current collectors are difficult to stretch under the roller pressure of cold pressing equipment alone, they are easy to stretch greatly under the squeezing of active materials, and there is a big difference in stretching with the active layer, which reduces the adhesion between the current collector and the edge of the active layer, and the active layer is prone to collapse, which leads to broken tape in the winding process, that is, fracture problems, which seriously reduce the quality of the pole piece and affect the battery performance. At the same time, more active materials have irregular angular structures, which are also easy to damage the current collector and reduce battery performance.

[0045] In the relevant technology, a layer of primer slurry can usually be applied between the active layer and the current collector, and a primer layer is formed after drying. The main components of the traditional anode primer slurry include sodium carboxymethyl cellulose, conductive carbon black and adhesive, while the main components of the cathode primer slurry include modified polyacrylate, calcium hydroxide and conductive carbon black. However, these primers can only increase the adhesion between the current collector and the active layer, and increase the conductivity of the pole piece. They cannot alleviate the extension problem of the current collector in the pole piece cold pressing process, and it is difficult to improve the active layer edge collapse, winding breakage, and damage to the current collector. It may be because these traditional primers themselves have a high hardness. In the case where the active layer contains hard carbon and other active materials with high hardness, which will not undergo structural slip under pressure and have an angular structure, these active materials squeeze each other during the cold pressing process, exerting pressure on the primer, and these pressures will still act on the current collector after being transmitted by the primer with higher hardness, thereby causing the current collector to have a large extension, and ultimately causing the active layer to collapse and the winding breakage. At the same time, the angular structures of these active materials may also pierce the bottom coating, thereby contacting the current collector and causing damage to the current collector.

[0046] In order to solve the problem of active layer edge collapse and winding breakage caused by large extension of the current collector (macroscopically manifested as large extension of the entire electrode), the embodiment of the present application provides a conductive buffer layer between the active layer of the electrode and the current collector, such as Figure 1 As shown in the right figure of , a specific carbon material is added to at least one of the conductive buffer layer and the active layer. These carbon materials can undergo internal structural slip and / or inter-particle slip under pressure. Then, during the cold pressing process, these carbon materials can slow down the squeezing effect of the active materials in the active layer on the current collector, so that the current collector will not be overly extended, thereby improving the problem of active layer edge collapse and winding breakage caused by large extension of the current collector.

[0047] The present application is further described below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present application and are not used to limit the scope of the present application.

[0048] A first aspect of an embodiment of the present application provides a pole piece, which includes a current collector, a conductive buffer layer and an active layer stacked in sequence, wherein at least one of the conductive buffer layer and the active layer contains a carbon material, and the carbon material includes one or more of graphite, soft carbon, and ethylene.

[0049] Among them, stacking in sequence refers to stacking two or more objects in sequence. In the embodiment of the present application, the pole piece includes a current collector, a conductive buffer layer, and an active layer stacked in sequence, that is, in a certain direction of the pole piece, the current collector, the conductive buffer layer, and the active layer are stacked in sequence in the order of current collector → conductive buffer layer → active layer; in the opposite direction, the current collector, the conductive buffer layer, and the active layer are stacked in sequence in the order of active layer → conductive buffer layer → current collector. That is, "including a current collector, a conductive buffer layer, and an active layer stacked in sequence" is also equivalent to "including an active layer, a conductive buffer layer, and a current collector stacked in sequence."

[0050] Considering that the current collector usually has two surfaces, the conductive buffer layer can be arranged on one or both surfaces of the current collector. In the case where the conductive buffer layer is arranged on one surface of the current collector, in one direction of the pole piece, the current collector, the conductive buffer layer and the active layer overlap in the order of current collector → conductive buffer layer → active layer; in the opposite direction, the current collector, the conductive buffer layer and the active layer overlap in the order of active layer → conductive buffer layer → current collector. In the case where the conductive buffer layer is arranged on both surfaces of the current collector, the current collector, the conductive buffer layer and the active layer overlap in the order of active layer → conductive buffer layer → current collector → conductive buffer layer → active layer, in which case the pole piece has a sandwich structure.

[0051] In an embodiment of the present application, a conductive buffer layer is provided between the current collector and the active layer, and carbon materials such as graphite, soft carbon, and footballene are provided in at least one of the conductive buffer layer and the active layer. These carbon materials have special structures and properties, and can undergo internal structural slip and / or inter-particle slip under pressure.

[0052] Specifically, in the crystal of graphite, carbon is arranged in an orderly and anisotropic manner, with carbon atoms in the same layer arranged in sp 2Hybridization forms covalent bonds, and each carbon atom is connected to three other atoms by three covalent bonds. The layers are mainly connected by molecular bonds, and the molecular attraction between the layers is weak. Therefore, graphite has the characteristics of soft particles, weak van der Waals force interaction between particles, and relative slippage between the layers during cold pressing. Similar to graphite, spherical carbon also has a layered structure, with molecular bonds between the layers, and weak molecular attraction between the layers. Relative slippage between the layers occurs during cold pressing. Soft carbon refers to amorphous carbon materials that can be graphitized at high temperatures above 2500°C, that is, amorphous carbon that is easily graphitized at high temperatures. The microcrystalline structure of soft carbon has lattice stripes, which are parallel straight stripes. At the same time, there is a large amount of amorphous carbon in the structure, and the crystal structure is relatively loose and disordered, and the layers are easy to slip during cold pressing.

[0053] Therefore, when the conductive buffer layer contains carbon material, the squeezing effect of the active material in the active layer on the current collector can be slowed down, the extension of the current collector can be reduced, and the extension difference between the current collector and the active layer can be reduced, and the problem of edge collapse of the active layer and the problem of winding broken tape can be improved. When the active layer contains carbon material, under the joint action of the conductive buffer layer and the carbon material, the squeezing effect of the active material in the active layer on the current collector can also be slowed down, and the problem of edge collapse of the active layer and the problem of winding broken tape can be finally improved.

[0054] At the same time, since the conductive buffer layer has a partitioning effect on the active layer and the current collector, the active material in the active layer does not directly contact the current collector, which can improve the damage of the active material to the current collector during the cold pressing process.

[0055] In some embodiments, the graphite may include one or more of artificial graphite and natural graphite.

[0056] In the graphite crystal, carbon is arranged in an orderly and anisotropic manner. The carbon atoms in the same layer are arranged in sp 2 Hybridization forms covalent bonds, and each carbon atom is connected to three other atoms by three covalent bonds. Molecular bonds are the main bonding between layers, and the molecular attraction between layers is weak. Therefore, the graphite particles are soft, and there is van der Waals force interaction between particles. The structure will slip during the cold pressing process, which can slow down the squeezing effect of the active material in the active layer on the current collector, reduce the extension of the current collector, and ultimately improve the problem of active layer edge collapse and winding broken belt; and the graphite morphology is regular and causes little damage to the current collector. In addition, graphite is easy to process and is easy to process and utilize; graphite is conductive, so it can also improve the conductivity of the pole piece.

[0057] In some embodiments, the Dv50 of the carbon material is 0.4-1.5 μm, optionally 0.7-0.9 μm, for example, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm, 0.8 μm, 0.85 μm, 0.9 μm, 0.95 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, any one of 1.5 μm or a range between any two of them.

[0058] In some embodiments, the Dv90 of the carbon material is 1-4 μm, optionally 1-3 μm, for example, any one of 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm or a range between any two of them.

[0059] The particle size distribution of materials is usually expressed as the percentage of particles in different particle size ranges. There are many benchmarks for measuring particle size distribution, such as number distribution, length distribution, area distribution, volume distribution, weight distribution, etc. Among them, volume distribution can usually be measured by laser method. Dv50 and Dv90 are specific particle size distributions based on volume distribution. Among them, Dv50 is the particle size corresponding to 50% of the volume distribution, and Dv90 is the particle size corresponding to 90% of the volume distribution.

[0060] The carbon material used in the embodiment of the present application has a smaller particle size, which is conducive to forming an extremely thin conductive buffer layer. Since the carbon material generally has a lower energy density than the active material in the active layer, when the conductive buffer layer contains the carbon material, the thinner the thickness of the conductive buffer layer is, the more conducive it is to reducing the energy density loss of the pole piece. Alternatively, the carbon material has a smaller particle size, which enables it to have good dispersibility in the active layer.

[0061] In some embodiments, the conductive buffer layer contains carbon material, and the mass content of the carbon material in the conductive buffer layer is greater than or equal to 5% and less than 100%, and optionally 14% to 56%. For example, the mass content of the carbon material in the conductive buffer layer is 5%, 14%, 15%, 18%, 20%, 25%, 28%, 30%, 35%, 40%, 45%, 50%, 55%, 56%, 60%, 70%, 80%, 90%, 95%, 98%, any one point value or any range value between two. Under the appropriate dosage, the structural characteristics of the carbon material can be fully utilized to slow down the squeezing effect of the active material in the active layer on the current collector, reduce the extension of the current collector, improve the problem of edge collapse of the active layer and the problem of winding broken belt, and reduce the damage to the current collector; and it is beneficial to reduce the energy density loss of the pole piece.

[0062] In some embodiments, the active layer contains carbon material, and the mass content of the carbon material in the active layer is 1% to 5%, optionally 3% to 5%, for example, any one of 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, and 5%, or any range between two of them. In the case where the active layer contains carbon material, considering that these carbon materials generally have lower energy density than the active material in the active layer, therefore, controlling the content of the carbon material in the active layer within a suitable range is conducive to reducing the energy density loss of the pole piece.

[0063] In some embodiments, the thickness of the conductive buffer layer is 3 to 6 μm, optionally 3 to 4 μm, for example, any point value of 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm or any range value between two of them. Generally, the thickness of the conductive buffer layer can be measured by a micrometer, a laser thickness gauge, a thickness scanning thickness gauge, etc. Since the carbon material generally has a lower energy density than the active material in the active layer (for example, the sodium storage density of the active material hard carbon is 380 to 450 mAh / g, while that of the soft carbon is only 160 to 240 mAh / g), when the conductive buffer layer contains carbon material, the conductive buffer layer has an extremely thin thickness, which is beneficial to reduce the energy density loss of the pole piece (under a fixed pole piece compaction density and thickness, the smaller the thickness of the conductive buffer layer, the greater the thickness of the active layer, the more active materials in the active layer, and the greater the energy density of the pole piece).

[0064] In some embodiments, the thickness of the active layer is 100-200 μm, optionally 130-150 μm, for example, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, or any point value or a range value between any two of them. The thickness of the active layer can be measured using a micrometer, a laser thickness gauge, a thickness scanning thickness gauge, etc. In the pole piece of the embodiment of the present application, the active layer can be set to a larger thickness, which is beneficial to increase the total amount of active material in the active layer, thereby reducing the energy density loss of the pole piece due to the incorporation of carbon material.

[0065] In some embodiments, the compaction density of the pole piece is 0.8 to 1 g / cm 3 , optionally 0.9~1g / cm 3 , for example 0.8 g / cm 3 , 0.82g / cm 3 , 0.84g / cm 3 , 0.85g / cm 3 , 0.9g / cm 3 , 0.92g / cm 3, 0.93g / cm 3 , 0.94g / cm 3 , 0.96g / cm 3 , 0.98g / cm 3 , 1g / cm 3 Any point value or any range value between the two. The compaction density of the pole piece can be obtained by using a compaction density meter and testing with reference to relevant standards such as GB / T 24533-2019. In the case where the conductive buffer layer of the embodiment of the present application has a thin thickness, by controlling the compaction density of the pole piece at a low level, the damage of the active material in the active layer to the current collector can be improved.

[0066] In some embodiments, the active layer comprises an active material, and the active material includes, but is not limited to, one or more of hard carbon, Prussian blue compounds, layered oxides, and polyanion compounds.

[0067] Hard carbon refers to carbon that is difficult to graphitize even at temperatures above 2500°C. It is usually prepared by thermal cracking of hard carbon precursors, such as polymer materials. Hard carbon precursors are often rich in heteroatoms such as hydrogen, oxygen, and nitrogen. During the heat treatment process, it is difficult for carbon to form sp 2 Hybridization results in its graphitization temperature usually being higher than 2500°C. Hard carbon particles are hard and brittle, with dispersed crystals, large lattice spacing, and irregular structures showing multiple edges and corners. Particles are mainly connected by weak mechanical rivets. There are COC chemical bonds with strong forces between the lamellar structures of hard carbon, that is, a multi-crosslinked structure between layers, and strong bonding between layers, so there is no slippage in the hard carbon structure during the cold pressing process.

[0068] Prussian blue compounds, including iron-based Prussian blue and manganese-based Prussian blue, have a stable cubic crystal structure and are not prone to structural slip under pressure.

[0069] The layered oxides include, but are not limited to, iron-based layered oxides, manganese-based layered oxides, iron-manganese-based layered oxides, and one or more of iron-based layered oxides, manganese-based layered oxides, and iron-manganese-based layered oxides doped with transition metal elements (such as Ti, Cu, and Ni). For example, iron-based layered oxides include, but are not limited to, NaFeO2, manganese-based layered oxides include, but are not limited to, NaMnO2, and iron-manganese-based layered oxides include, but are not limited to, Na x Fe y Mn 1-y O2 (x=0.2~1, y=0.1~0.9, such as Na 0.67 Fe 0.5 Mn 0.5 O2, Na 0.67 Fe 0.45 Mn 0.65O2). The atoms in layered oxides have strong interactions, good structural stability, and are not prone to structural slip under pressure.

[0070] Polyanion compounds may include but are not limited to one or more of phosphates, pyrophosphates, fluorophosphates, and mixed phosphates, wherein phosphates include but are not limited to one or more of Na3V2(PO4)3 and Na4MnV(PO4)3, pyrophosphates include but are not limited to one or more of NaFeP2O7, NaMnP2O7, and NaCoP2O7, fluorophosphates include but are not limited to NaVPO4F, and mixed phosphates include but are not limited to one or more of Na4Fe3(PO4)2P2O7 and Na4Mn3(PO4)2P2O7. Polyanion electrode materials have a stable polyhedral framework structure, and are not prone to structural slippage under pressure.

[0071] Therefore, during the cold pressing process, these active materials squeeze each other and exert a certain pressure on the current collector. Under the squeezing of the active materials, the current collector area coated with the active materials is prone to large extension, and there is a large difference in extension with the active layer, which reduces the bonding force between the edge of the current collector and the active layer, and easily causes the active layer to collapse, which leads to broken tape in the winding process, that is, fracture problems, which seriously reduces the quality of the pole piece. At the same time, these angular structures of the active materials are also prone to damage the current collector. The embodiment of the present application provides a conductive buffer layer and adds carbon material for the pole piece with such active materials, which can improve the above-mentioned active layer collapse and broken tape problems.

[0072] In some embodiments, the mass content of the active material in the active layer is 85% to 90%, optionally 85% to 87%, such as 85%, 86%, 87%, 88%, 89%, 90% or any point value or a range of values ​​between any two of them. The active material participates in the transfer of electrons and ions in the electrochemical reaction, affects the energy density and other electrochemical properties of the pole piece, and helps to improve the electrochemical properties of the pole piece at a suitable active material content.

[0073] In some embodiments, the conductive buffer layer and the active layer may also independently contain a conductive agent. In the case where the conductive buffer layer contains a carbon material, the conductive buffer layer may additionally contain a conductive agent or may not contain a conductive agent. Adding a conductive agent to the conductive buffer layer can enhance the electron transfer between the active layer and the current collector and improve the conductivity of the pole piece. In the active layer, the conductive agent can enhance the electron transfer within the active layer and between the active layer and the conductive buffer layer, thereby improving the conductivity of the pole piece.

[0074] In some embodiments, the conductive agents in the conductive buffer layer and the active layer independently include, but are not limited to, one or more of acetylene black, carbon nanotubes, conductive carbon black (super-P, sp), Ketjen black, carbon fiber, and graphene. These conductive agents have excellent conductive properties and are easy to obtain. For example, the conductive carbon black used in traditional processes usually contains primary particles with a diameter of about 40nm agglomerated into primary aggregates of 150 to 200nm, which are often dispersed around active materials to form a multi-branched conductive network, thereby reducing the physical internal resistance of the battery and improving electronic conductivity; or applied to the primer to improve the conductivity of the active material and the current collector.

[0075] In some embodiments, the mass content of the conductive agent in the conductive buffer layer is 0-56%, optionally 20%-42%, such as 0%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 42%, 45%, 50%, 55%, 56%, or any point value or a range value between any two of them. Adding a conductive agent to the conductive buffer layer can enhance the electron transfer between the active layer and the current collector and improve the conductivity of the pole piece.

[0076] In some embodiments, the mass content of the conductive agent in the active layer includes but is not limited to 1% to 5%, optionally 2% to 3%, such as 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, any one point value or any range value between two, and can also be set to other contents as needed. Adding a suitable amount of conductive agent to the active layer can enhance the electron transmission inside the active layer and between the active layer and the conductive buffer layer, and improve the conductivity of the electrode.

[0077] In some embodiments, the conductive buffer layer and the active layer each independently further comprise an adhesive. In the conductive buffer layer, the adhesive is used to enhance the bonding force between the conductive buffer layer and the current collector, between the conductive buffer layer and the active layer, and between the materials in the conductive buffer layer. In the active layer, the adhesive can enhance the bonding force between the conductive buffer layer and the active layer, and between the materials in the active layer.

[0078] In some embodiments, the adhesive in the conductive buffer layer and the active layer independently includes one or more of an oil-soluble adhesive, a water-soluble adhesive, and an emulsion adhesive. The oil-soluble adhesive includes one or more of polyvinylidene fluoride, polyimide, polytetrafluoroethylene, polybutyl acrylate, and polyacrylonitrile. The water-soluble adhesive includes one or more of carboxymethyl cellulose, carboxymethyl cellulose salt, polyacrylic acid, polyacrylic acid salt, polyvinyl alcohol, sodium alginate, and cyclodextrin. The emulsion adhesive includes one or more of styrene-butadiene rubber, vinyl acetate resin, acrylic resin, and chlorinated rubber.

[0079] In some embodiments, the mass content of the adhesive in the conductive buffer layer is 35% to 45%, optionally 40% to 42%, for example, any point value among 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45% or a range value between any two of them.

[0080] In some embodiments, the mass content of the adhesive in the active layer independently includes but is not limited to 0.5% to 10%, such as 5% to 9%, for example, any point value of 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range value between any two of them, and can also be set to other contents as needed.

[0081] In some embodiments, the conductive buffer layer and the active layer may also optionally and independently include a thickener, such as carboxymethyl cellulose (CMC). The mass content of the thickener in the conductive buffer layer and the active layer may independently include, but is not limited to, 0.5% to 5%, such as 1% to 5%, such as 0.5%, 1%, 2%, 3%, 4%, 5%, or any point value or a range value between any two of them, and may also be set to other contents as needed. By adding a thickener, the viscosity of the conductive buffer layer and the active layer-related slurry may be adjusted to make it easier to process and manufacture.

[0082] In some embodiments, the current collector includes but is not limited to a metal current collector, a carbon current collector, a conductive resin current collector, a composite current collector of metal and resin, etc., more specifically, copper, aluminum, nickel, titanium, iron and their respective alloys, stainless steel, carbon fiber, carbon nanotube (CNT), graphite, etc. The current collector on the pole piece is used to combine with the active layer and transmit electrons in the battery chemical reaction.

[0083] In some embodiments, the thickness of the current collector includes but is not limited to 6 to 13 μm, optionally 6 to 10 μm, such as 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, or any point value or a range value between any two. The thickness of the current collector can be measured using a micrometer, a laser thickness gauge, a thickness scanning thickness gauge, etc. At a smaller current collector thickness, it is beneficial to reduce the mass of the pole piece and meet the market's requirements for lightweight pole pieces.

[0084] In some embodiments, the electrode sheet includes one or both of a positive electrode sheet and a negative electrode sheet. The technical solution of the embodiment of the present application is applicable to different electrode sheets and has good applicability.

[0085] The second aspect of an embodiment of the present application provides a method for preparing a pole piece, comprising the steps of: preparing a conductive buffer layer on the surface of a current collector; preparing an active layer on the surface of the conductive buffer layer; wherein at least one of the conductive buffer layer and the active layer comprises a carbon material, and the carbon material comprises one or more of graphite, soft carbon, and ethylene.

[0086] In the embodiment of the present application, a conductive buffer layer and an active layer are sequentially prepared on the surface of a current collector to obtain a pole piece including a current collector, a conductive buffer layer and an active layer stacked in sequence, and the preparation method is simple.

[0087] In some embodiments, the step of preparing the conductive buffer layer includes: providing a primer slurry, and coating the primer slurry on the surface of the current collector.

[0088] In some embodiments, the viscosity of the primer slurry is 100-1000 mPa / s (25° C.), optionally 300-600 mPa / s, such as 100 mPa / s, 200 mPa / s, 300 mPa / s, 400 mPa / s, 500 mPa / s, 600 mPa / s, 700 mPa / s, 800 mPa / s, 900 mPa / s, 1000 mPa / s, or any range between two values. The viscosity can be obtained by testing under specific conditions using a viscosity tester. Appropriate slurry viscosity is helpful for the processing and production of the conductive buffer layer.

[0089] In some embodiments, the primer slurry may contain a carbon material. The primer slurry may also contain one or more of an adhesive and a conductive agent; the preparation method of the primer slurry includes mixing one or more of the adhesive and the conductive agent with the carbon material, and dispersing the mixture with a solvent to obtain the primer slurry; or, dispersing the adhesive and the conductive agent with a solvent to obtain the primer slurry. Among them, the mixing process may adopt one or both of dry mixing and wet mixing. During the mixing process, a rotation speed of 200 to 1200 rpm may be used for 5 to 30 minutes; the solvents used include but are not limited to water, NMP (N-methylpyrrolidone), DMF (dimethylformamide), EGDME (ethylene glycol dimethyl ether), EC (ethylene carbonate), mineral oil, ethanol, and acetone. One or more; the time for dispersing the mixture with a solvent may be set to 30 to 90 minutes, and the dispersion process may be assisted by stirring or may not be stirred.

[0090] In some embodiments, the step of preparing the active layer includes: providing an active slurry containing an active material, and coating the active slurry on the surface of the conductive buffer layer.

[0091] In some embodiments, the solid content of the active slurry is 45% to 55%, optionally 50% to 55%, for example, any one of 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55% or any range between two of them. The solid content can be obtained by testing with a moisture meter; or by testing with a drying method, that is, by weighing the mass of the slurry before and after drying to calculate the solid content. The active slurry is conducive to the processing and production of the active layer at a suitable solid content.

[0092] In some embodiments, the viscosity of the active slurry is 4000-15000 mPa / s (25° C.), optionally 8000-12000 mPa / s, such as 4000 mPa / s, 6000 mPa / s, 8000 mPa / s, 10000 mPa / s, 12000 mPa / s, 14000 mPa / s, 15000 mPa / s, or any range between two values. The viscosity can be obtained by testing under specific conditions using a viscosity tester. Appropriate slurry viscosity is helpful for the processing and production of the active layer.

[0093] In some embodiments, the active slurry may contain a carbon material. The active slurry may also contain one or more of an adhesive and a conductive agent; the preparation method of the active slurry includes mixing one or more of the adhesive and the conductive agent with the active material, and dispersing the mixture with a solvent to obtain an active slurry; or, mixing one or more of the adhesive and the conductive agent with the active material and the carbon material, and dispersing the mixture with a solvent to obtain an active slurry. Among them, the mixing process may adopt one or both of dry mixing and wet mixing. During the mixing process, a rotation speed of 200 to 1200 rpm may be used for 5 to 30 minutes; the solvents used include but are not limited to one or more of water, NMP (N-methylpyrrolidone), DMF (dimethylformamide), EGDME (ethylene glycol dimethyl ether), EC (ethylene carbonate), mineral oil, ethanol, and acetone; the time for dispersing the mixture with a solvent may be set to 30 to 90 minutes, and the dispersing process may be assisted by stirring or may not be stirred.

[0094] In some embodiments, in the steps of preparing the conductive buffer layer and preparing the active layer, the coating methods used may independently include but are not limited to one or more of printing, spin coating, and roller coating.

[0095] In some embodiments, the method for preparing the pole piece further includes the step of drying the conductive buffer layer and / or the active layer. After the primer slurry and / or the active slurry are coated, they usually need to be dried to volatilize the solvent therein, to form a solid conductive buffer layer and / or active layer, and to enhance the bonding force between the conductive buffer layer, the active layer and the current collector. In actual operation, the primer slurry can be coated on the surface of the current collector and then dried for the first time; then, after the active slurry is coated on the surface of the conductive buffer layer, a second drying process is performed. Alternatively, after the primer slurry is coated on the surface of the current collector, the active slurry can be directly coated and then dried. That is, the drying process of the conductive buffer layer and the active layer can be performed successively or simultaneously. The drying process includes, but is not limited to, one or more of heating, air cooling, natural drying, and freeze drying.

[0096] In some embodiments, the method for preparing the pole piece also includes the step of forming the pole piece. The forming method includes one or both of cold pressing and hot pressing, and optionally includes cold pressing. By performing forming treatments such as cold pressing or hot pressing on the pole piece, the density of the pole piece can be improved and the bonding force between the conductive buffer layer, the active layer, and the current collector can be enhanced. The pressure used in the forming step may include 20 to 80T, for example, any one of 20T, 30T, 40T, 50T, 60T, 70T, 80T or a range of values ​​between any two. In some embodiments, the method for preparing the pole piece also includes the step of cutting the pole piece. According to actual needs, the pole piece is cut into various required shapes to make it suitable for different application scenarios.

[0097] A third aspect of an embodiment of the present application provides a battery, which includes the above-mentioned electrode piece, or includes the electrode piece prepared by the above-mentioned method.

[0098] The pole piece of the embodiment of the present application can reduce the extension of the current collector under the action of the carbon material and the conductive buffer layer, improve the problem of active layer edge collapse and winding belt breakage, and the current collector is less damaged, so this pole piece has good structural stability. After the pole piece with a stable structure of the embodiment of the present application is applied to the battery, the active layer is not prone to fall off and powdering during the battery charging and discharging process, which will help improve the battery cycle stability.

[0099] In some embodiments, the battery of the embodiment of the present application includes one or more of a primary battery and a secondary battery. Batteries can be divided into primary batteries and secondary batteries according to whether the battery can be recharged and reused. A primary battery cannot be recharged to restore it after discharge, and a secondary battery can continue to be used by activating the active material by charging after the battery is discharged. The pole piece of the embodiment of the present application can be applied to both primary batteries and secondary batteries, and has a wide range of uses.

[0100] In some embodiments, the battery of the embodiments of the present application includes one or more of a battery cell, a battery module, and a battery pack. In the case where the battery is a secondary battery, the secondary battery is divided into a battery cell, a battery module, and a battery pack according to different packaging forms. Among them, the battery cell is the most basic unit of a secondary battery, including an electrode assembly and an electrolyte. The electrode assembly is usually composed of a positive electrode sheet, a negative electrode sheet, and a separator. The battery cell mainly relies on the movement of metal ions in the electrolyte between the positive electrode sheet and the negative electrode sheet to work. In some battery packaging technologies, multiple battery cells can be integrated into a battery module first, and then the battery module can be installed in the battery box to form a battery pack. In other battery packaging technologies, multiple battery cells can also be directly installed in the box to form a battery pack, eliminating the intermediate state of the battery module, thereby reducing the mass of the battery pack and increasing the energy density of the battery.

[0101] In some embodiments, the battery may include one or more of a sodium ion battery, a lithium ion battery, a lithium sulfur battery, a sodium lithium ion battery, and a magnesium ion battery.

[0102] In some embodiments, the battery of the embodiment of the present application includes the above-mentioned electrode sheet, which can be a positive electrode sheet or a negative electrode sheet, or can include both a positive electrode sheet and a negative electrode sheet.

[0103] In some embodiments, the battery further includes an electrolyte. The electrolyte can serve as a carrier for ion transport in the battery.

[0104] In some embodiments, the electrolyte may be a solid electrolyte, including but not limited to a polymer electrolyte, an inorganic solid electrolyte, etc. The electrolyte may also be an electrolyte solution. As the electrolyte solution, a solvent and a metal salt dissolved in the solvent may be included.

[0105] Among them, the solvent in the electrolyte may include a non-aqueous organic solvent, for example, one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB) and ethyl butyrate (EB), preferably including two or more.

[0106] The metal salt may include one or more of a sodium salt and a lithium salt.

[0107] The sodium salt may include one or more of sodium hexafluorophosphate (NaPF6), sodium chlorate (NaClO4), sodium chloride (NaCl), sodium tetrafluoroborate (NaBF4), sodium nitrate (NaNO3), sodium cyanide (NaCN), sodium bisulfate (NaHSO4), sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), and sodium bis(trifluoromethylsulfonyl)imide (NaFSI).

[0108] The lithium salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium bis(oxalatoborate) (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP), for example, one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium bis(fluorosulfonyl)imide (LiFSI).

[0109] The electrolyte may also contain other additives, such as vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), succinonitrile (SN), adiponitrile (ADN), glutaronitrile (GLN), hexanetrinitrile (HTN), 1,3-propane sultone (1,3-PS), vinyl sulfate (DTD), methylene disulfonate (MMDS), 1-propylene-1,3-sultone (PST), 4-methylethylene sulfate (PCS), 4-ethylethylene sulfate (PES), 4-propylethylene sulfate (PEGLST), propylene sulfate (TS), 1,4-butane sultone (1,4-BS), ethylene sulfite (DTO), dimethyl sulfite (DMS), diethyl sulfite (DES), sulfonate cyclic quaternary ammonium salt, tris(trimethylsilyl) phosphate (TMSP) and tris(trimethylsilyl) borate (TMSB), but are not limited thereto.

[0110] In some embodiments, the battery further includes a separator stacked between the positive electrode sheet and the negative electrode sheet. In some batteries, a separator is required to separate the positive electrode sheet from the negative electrode sheet so that electrons in the battery cannot pass freely, preventing the two electrodes from contacting and short-circuiting, while allowing ions in the electrolyte to pass freely between the positive and negative electrodes.

[0111] The isolation membrane can be any known porous structure isolation membrane with electrochemical stability and mechanical stability, including but not limited to single-layer or multi-layer films of one or more of glass fiber, non-woven fabric, polyethylene (PE), polypropylene (PP) and polyvinylidene fluoride (PVDF).

[0112] The positive electrode sheets and the negative electrode sheets are alternately stacked, and a separation film is set between the positive electrode sheets and the negative electrode sheets to play an isolating role, so as to obtain a battery cell, or the battery cell can be obtained after winding. The battery cell is placed in a casing, an electrolyte is injected, and it is sealed to obtain a battery cell. Multiple battery cells are first integrated to form a battery module, which can provide higher voltage and capacity, and has a specific functional output; then the battery module is installed in the battery box, and a battery management system is usually added to form a battery pack, which is usually a product provided to users. Alternatively, multiple battery cells can be directly installed in the box to form a battery pack.

[0113] refer to Figure 2 , which is an example of a battery module 4. In the battery module 4, a plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0114] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0115] refer to Figure 3 and Figure 4 , which is taken as an example of a battery pack 1. The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, and the upper box body 2 can be covered on the lower box body 3 to form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0116] In some embodiments, the battery may include an outer packaging, which may be used to encapsulate the electrode assembly consisting of the positive electrode sheet, the negative electrode sheet, the separator, and the electrolyte.

[0117] The outer packaging of the battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0118] The shape of the battery can be cylindrical, square or any other shape. For example, Figure 5 A square-structured battery is used as an example.

[0119] In some embodiments, reference Figure 6 The outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate are enclosed to form a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process or a lamination process. One or more electrode assemblies 52 are encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52.

[0120] The embodiment of the present application also provides an electrical device, which includes the above-mentioned battery. The battery disclosed in the embodiment of the present application can be used to provide electrical energy for various electrical devices. The electrical device may include but is not limited to mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, etc. Among them, electric toys may include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys and electric airplane toys, etc., and spacecraft may include airplanes, rockets, space shuttles and spacecraft, etc. As the above-mentioned electrical device, the battery cell, battery module or battery pack in the battery can be selected according to its use requirements.

[0121] Figure 7 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the battery, a battery pack or a battery module can be used.

[0122] The following describes the invention in conjunction with specific embodiments.

[0123] Example 1

[0124] This embodiment provides a pole piece, including an active layer, a conductive buffer layer, a current collector, a conductive buffer layer and an active layer stacked in sequence. That is, the pole piece includes a current collector, conductive buffer layers are arranged on both surfaces of the current collector, and an active layer is arranged on the surface of the conductive buffer layer. The current collector is a 6μm thick Cu foil; the conductive buffer layer contains carboxymethyl cellulose (CMC) with a mass content of 3%, 41%, and 56%, respectively, an adhesive (styrene butadiene rubber, SBR) and graphite (Dv50 = 0.8μm, Dv90 = 2μm), with a total thickness of 3μm; the active layer contains hard carbon, a conductive agent (conductive carbon black, sp) and an adhesive SBR with a mass content of 90%, 3%, and 7%, respectively, with a total thickness of 142μm.

[0125] In this embodiment, the method for preparing the electrode comprises the following steps:

[0126] 1) CMC, SBR and graphite were dry mixed at 1200 rpm for 5 min according to the proportion, and then water was added for dispersion for 60 min to prepare a primer slurry with a viscosity controlled at 100 mPa / s (25° C., Brookfield DV2T viscometer, No. 63 rotor).

[0127] 2) The prepared primer slurry is coated on the Cu foil by using the gravure technology, and a conductive buffer layer is formed on both surfaces of the Cu foil after drying.

[0128] 3) Mix hard carbon, sp and SBR as an adhesive in proportion, add water to prepare an active slurry with a solid content of 55%, apply the active slurry on the surface of the conductive buffer layer, dry and cold press to obtain a pole piece.

[0129] Example 2

[0130] This embodiment provides a pole piece, which is different from the first embodiment only in that the graphite is replaced by soft carbon of equal mass (Dv50=0.8 μm, Dv90=2 μm). The rest is the same as the first embodiment.

[0131] Example 3

[0132] This embodiment provides a pole piece, which is different from the embodiment 1 in that sp is added to the conductive buffer layer and the content of graphite is reduced. Specifically, in this embodiment, the conductive buffer layer contains CMC, SBR, graphite (Dv50 = 0.8 μm, Dv90 = 2 μm) and sp in mass contents of 3%, 41%, 14%, and 42%, respectively. The rest is the same as the embodiment 1.

[0133] Example 4

[0134] This embodiment provides a pole piece, which is different from the embodiment 3 in that the mass content of graphite in the conductive buffer layer is increased, and the mass content of sp in the conductive buffer layer is reduced. Specifically, in this embodiment, the conductive buffer layer contains CMC, SBR, graphite (Dv50 = 0.8 μm, Dv90 = 2 μm) and sp in mass contents of 3%, 41%, 28%, and 28%, respectively. The rest is the same as the embodiment 3.

[0135] Example 5

[0136] This embodiment provides a pole piece, which is different from the embodiment 4 in that the Cu foil is replaced by an Al foil with a thickness of 13 μm. The rest is the same as the embodiment 4.

[0137] Example 6

[0138] This embodiment provides a pole piece, which is different from the embodiment 4 in that the particle size of graphite is reduced. Specifically, the particle size of graphite in the conductive buffer layer of this embodiment is: Dv50 = 0.4 μm, Dv90 = 1 μm. Others are the same as the embodiment 4.

[0139] Example 7

[0140] This embodiment provides a pole piece, which is different from the embodiment 4 in that the particle size of graphite is increased, and the increase in the particle size of graphite increases the thickness of the conductive buffer layer. Specifically, the particle size of graphite in the conductive buffer layer of this embodiment is: Dv50 = 1.5 μm, Dv90 = 4 μm, and the total thickness of the conductive buffer layer is 6 μm. Others are the same as the embodiment 4.

[0141] Example 8

[0142] This embodiment provides a pole piece, which is different from the embodiment 4 in that the graphite is replaced by soft carbon of equal mass (Dv50=0.8 μm, Dv90=2 μm). The rest is the same as the embodiment 4.

[0143] Example 9

[0144] This embodiment provides a pole piece, which is different from the embodiment 4 in that the conductive buffer layer contains graphite, soft carbon and sp at the same time. Specifically, in this embodiment, the conductive buffer layer contains CMC, SBR, graphite (Dv50 = 0.8 μm, Dv90 = 2 μm), soft carbon (Dv50 = 0.8 μm, Dv90 = 2 μm) and sp with a mass content of 3%, 41%, 18%, 18%, and 20%, respectively. The rest is the same as the embodiment 4.

[0145] Example 10

[0146] This embodiment provides a pole piece, including a current collector, conductive buffer layers are arranged on both surfaces of the current collector, and an active layer is arranged on the surface of the conductive buffer layer. The current collector is a Cu foil with a thickness of 6 μm; the conductive buffer layer contains CMC, SBR and sp with a mass content of 3%, 41% and 56% respectively; the active layer contains graphite (Dv50 = 0.8 μm, Dv90 = 2 μm), hard carbon, sp and SBR with a mass content of 1%, 89%, 3% and 7% respectively, and the total thickness is 142 μm.

[0147] In this embodiment, the method for preparing the electrode comprises the following steps:

[0148] 1) CMC, SBR and sp were dry mixed at 1200 rpm for 5 min according to the proportion, and then water was added for dispersion for 60 min to prepare a primer slurry with a viscosity controlled at 100 mPa / s (25° C., Brookfield DV2T viscometer, No. 63 rotor).

[0149] 2) The prepared primer slurry is coated on the Cu foil by using the gravure technology, and a conductive buffer layer is formed on both surfaces of the Cu foil after drying.

[0150] 3) Graphite, hard carbon, sp and SBR are mixed according to proportion, and water is added to prepare an active slurry with a solid content of 55%. The active slurry is coated on the surface of the conductive buffer layer, and the electrode is obtained after drying and cold pressing.

[0151] Embodiment 11

[0152] This embodiment provides a pole piece, which is different from the embodiment 10 in that the mass content of graphite in the active layer is increased. Specifically, in this embodiment, the active layer contains graphite (Dv50 = 0.8 μm, Dv90 = 2 μm), hard carbon, sp and SBR with mass contents of 3%, 87%, 3% and 7%, respectively. The rest is the same as the embodiment 10.

[0153] Example 12

[0154] This embodiment provides a pole piece, which is different from the embodiment 10 in that the mass content of graphite in the active layer is increased. Specifically, in this embodiment, the active layer contains graphite (Dv50 = 0.8 μm, Dv90 = 2 μm), hard carbon, sp and SBR with mass contents of 5%, 85%, 3% and 7%, respectively. The rest is the same as the embodiment 10.

[0155] Embodiment 13

[0156] This embodiment provides a pole piece, which is different from the embodiment 11 in that the Cu foil is replaced by an Al foil with a thickness of 13 μm. The rest is the same as the embodiment 11.

[0157] Embodiment 14

[0158] This embodiment provides a pole piece, which is different from the embodiment 11 in that the graphite is replaced by soft carbon of equal mass (Dv50=0.8 μm, Dv90=2 μm). The rest is the same as the embodiment 11.

[0159] Embodiment 15

[0160] This embodiment provides a pole piece, which is different from the embodiment 14 in that the Cu foil is replaced by an Al foil with a thickness of 13 μm. The rest is the same as the embodiment 14.

[0161] Comparative Example 1

[0162] This comparative example provides a pole piece, which is mainly different from the various embodiments in that the conductive buffer layer and the active layer do not contain graphite or soft carbon.

[0163] Specifically, the pole piece of this comparative example includes a current collector, and a conductive buffer layer is arranged on both surfaces of the current collector, and an active layer is arranged on the surface of the conductive buffer layer. The current collector is a Cu foil with a thickness of 6 μm; the conductive buffer layer contains CMC, SBR and sp with a mass content of 3%, 41% and 56% respectively, and a total thickness of 3 μm; the active layer contains hard carbon, sp and SBR with a mass content of 90%, 3% and 7% respectively, and a total thickness of 142 μm.

[0164] Comparative Example 2

[0165] This comparative example provides a pole piece, which is different from comparative example 1 in that the Cu foil is replaced by an Al foil with a thickness of 13 μm. Other aspects are the same as comparative example 1.

[0166] Comparative Example 3

[0167] This comparative example provides a pole piece, which is mainly different from the various embodiments in that it does not contain a conductive buffer layer, graphite, or soft carbon.

[0168] Specifically, the pole piece of this comparative example includes a current collector, and active layers are arranged on both surfaces of the current collector. The current collector is a Cu foil with a thickness of 6 μm; the active layer contains hard carbon, sp and SBR with mass contents of 90%, 3% and 7% respectively, and the total thickness is 142 μm.

[0169] Comparative Example 4

[0170] This comparative example provides a pole piece, which is different from comparative example 3 in that the Cu foil is replaced by an Al foil with a thickness of 13 μm. The other parts are the same as comparative example 3.

[0171] The electrode compositions of various embodiments and comparative examples are shown in the following table.

[0172] Table 1. Electrode composition

[0173]

[0174]

[0175]

[0176] The compaction density of the pole pieces of each embodiment and comparative example is fixed at 0.93 g / cm 3, and test its elongation (the elongation of the pole piece depends largely on the elongation of the current collector, so the elongation of the pole piece can reflect the elongation of the current collector). Using these pole pieces with fixed compaction density as the negative electrode, NaFeO2 as the positive electrode, and PP isolation film, the negative electrode, positive electrode and isolation film are wound into a bare battery cell, and then the battery cell is placed in an aluminum-plastic film package, and then the top and side sealing process is carried out, and then the electrolyte (1mol / LNaPF6; EC, DMC=1:1, v:v) is injected, and then the sodium ion battery soft pack is obtained through static, shaping, and formation processes, and the first effect and cycle performance tests are carried out. The results are shown in the following table.

[0177] Table 2. Pole performance test results

[0178]

[0179]

[0180] In Table 2, the elongation ratio 1 refers to the percentage of the elongation of the pole piece of each embodiment to the elongation of the pole piece of Comparative Example 1 (or Comparative Example 2) when the same current collector is used.

[0181] For example, the current collector used in Example 1 is a 6μm thick Cu foil, and the elongation of its pole piece is 1.20%; while Comparative Example 1 also uses a 6μm thick Cu foil as the current collector, and the elongation of its pole piece is 2.80%, then the elongation ratio 1 corresponding to Example 1 = the elongation of the pole piece of Example 1 / the elongation of the pole piece of Comparative Example 1*100%=1.20% / 2.80%*100%=42.86%. For another example, the current collector used in Example 5 is a 13μm thick Al foil, and the elongation of its pole piece is 0.38%; while Comparative Example 2 also uses a 13μm thick Al foil as the current collector, and the elongation of its pole piece is 2.10%, then the elongation ratio 1 corresponding to Example 5 = the elongation of the pole piece of Example 5 / the elongation of the pole piece of Comparative Example 2*100%=0.38% / 2.10%*100%=18.10%.

[0182] The elongation ratio 2 refers to the percentage of the elongation of each embodiment, comparative example 1, comparative example 2 to the elongation of comparative example 3 (or comparative example 4) when the same current collector is used.

[0183] For example, the current collector used in Example 1 is a 6μm thick Cu foil, and the elongation of its pole piece is 1.20%; while Comparative Example 3 also uses a 6μm thick Cu foil as the current collector, and the elongation of its pole piece is 3.40%, then the elongation ratio 2 corresponding to Example 1 = the elongation of the pole piece of Example 1 / the elongation of the pole piece of Comparative Example 3*100%=1.20% / 3.40%*100%=35.29%. For another example, the current collector used in Example 5 is a 13μm thick Al foil, and the elongation of its pole piece is 0.38%; while Comparative Example 4 also uses a 13μm thick Al foil as the current collector, and the elongation of its pole piece is 3.80%, then the elongation ratio 2 corresponding to Example 5 = the elongation of the pole piece of Example 5 / the elongation of the pole piece of Comparative Example 4*100%=0.38% / 3.80%*100%=10.00%.

[0184] The test results show:

[0185] The pole pieces of Comparative Examples 3 and 4 adopt the traditional pole piece structure, and only the active layer is prepared on the current collector, and the active layer does not contain graphite or soft carbon. 3 It has a very high elongation (reaching 3.40% and 3.80%), and is prone to edge collapse and winding breakage; and the cycle performance is poor (after 450 and 580 cycles at 45°C, the capacity drops to 80%). Although Comparative Examples 1 and 2 add a conductive buffer layer containing CMC, adhesive and sp between the current collector and the active layer on the basis of Comparative Examples 3 and 4, the conductive buffer layer of this composition has little effect on improving the ductility of the electrode (55.26% to 82.35% of Comparative Examples 3 and 4), and is still prone to edge collapse and winding breakage, that is, there is a problem of structural instability, which makes the cycle performance of the electrode not effectively improved.

[0186] In contrast, Examples 1 to 15 can effectively reduce the elongation of the pole piece by providing a conductive buffer layer between the current collector and the active layer, and adding graphite and soft carbon to the conductive buffer layer or the active layer. At the same compaction density, the elongation is reduced to 0.38% to 1.50%. Comparison shows that the elongation is only 8.82% to 44.12% of Comparative Examples 3 and 4, and 10.71% to 66.67% of Comparative Examples 1 and 2. Such a low elongation can effectively improve the problems of pole piece edge collapse and winding breakage, and at the same time improve the cycle performance of the pole piece, so that the capacity of the pole piece is reduced to 80% after 870 to 1360 cycles at 45°C.

[0187] More specifically, in Examples 1 to 9, a conductive buffer layer is provided between the active layer and the current collector, wherein the conductive buffer layer of Examples 1 and 2 contains up to 56% by mass of graphite or soft carbon, so that the elongation of the pole piece is reduced to 1.20% and 1.50%, and the number of cycles with a capacity retention rate of 80% at 45°C is increased to 870 and 980. In Examples 3 to 9, by reducing the content of graphite or soft carbon in the conductive buffer layer and adding sp to the conductive buffer layer, the elongation of the pole piece can be further reduced to 0.30% to 0.90%, which is only 10.71% to 32.14% of Comparative Examples 1 and 2, and 8.82% to 26.47% of Comparative Examples 3 and 4.

[0188] Examples 1 to 9 also reflect that the elongation of the pole piece has a large correlation with the mass content of graphite (or soft carbon) in the conductive buffer layer. Within a certain range, the elongation of the pole piece first decreases and then increases as the content of graphite (or soft carbon) in the conductive buffer layer decreases. For example, in Examples 4 to 9, the content of graphite (or soft carbon) in the conductive buffer layer is lower than that in Examples 1 and 3, and the elongation of the pole piece is lower than that in Examples 1 and 3; in Example 3, the content of graphite in the conductive buffer layer is further reduced compared with Examples 4 to 9, and the elongation of the pole piece has increased slightly. At the same time, Examples 5 to 7 reflect that the elongation of the pole piece is correlated with the particle size of graphite (or soft carbon). Within a certain range, the elongation of the pole piece decreases as the particle size of graphite (or soft carbon) increases. Therefore, the elongation of the pole piece can be further optimized by optimizing the particle size of graphite (or soft carbon). However, in the cases where the conductive buffer layer of Examples 1 to 9 contains graphite (or soft carbon), the elongation is lower than that of the pole piece without graphite (or soft carbon).

[0189] In Examples 10 to 15, a traditional conductive buffer layer is arranged between the active layer and the current collector, and a certain amount of graphite or soft carbon is added to the active layer, so that the elongation of the pole piece is reduced to 0.80% to 1.50%, and the number of cycles with a capacity retention rate of 80% at 45°C is increased to 1054 to 1145 cycles, which is significantly improved compared with Comparative Examples 1 to 4. At the same time, it can be seen from Examples 10 to 12 that the elongation of the pole piece has a large correlation with the mass content of graphite (or soft carbon) in the active layer. Within a certain range, the elongation of the pole piece decreases with the increase of the content of graphite (or soft carbon) in the active layer.

[0190] In addition, analysis of the first effect revealed that in Examples 1 to 15, after a conductive buffer layer was set between the current collector and the active layer and graphite or soft carbon was added to the conductive buffer layer or the active layer, the electrode had a higher first effect, which was similar to the first effect of the common sodium ion battery using a hard carbon negative electrode, reflecting that the setting of the conductive buffer layer, graphite, and soft carbon did not cause a significant degradation of the first effect.

[0191] In summary, by setting a conductive buffer layer between the current collector and the active layer of the pole piece, and adding graphite and soft carbon to at least one of the conductive buffer layer and the active layer, the elongation of the pole piece can be effectively reduced; by adjusting the content of graphite and soft carbon in the conductive buffer layer and the active layer, the elongation of the pole piece can be further optimized. In practice, the reduction of the elongation of the pole piece can effectively improve the stability of the pole piece, improve the edge collapse of the pole piece and the problem of winding broken belt, which is conducive to improving the cycle performance of the battery.

[0192] Appendix: The relevant performance test methods are as follows:

[0193] 1) Pole elongation

[0194] Take three sections of anode pole pieces, remove the pole ear area, and make three horizontal marking points at intervals of three meters along the pole piece direction. The length of the two marking points is accurate to 0.1mm, and the length is recorded as a (respectively a1, a2, a3); adjust the left and right gaps of the cold press and the tonnage of the roller (20T~79T) so that the cold pressed thickness meets the set compaction density; measure the length b of the pole piece mark after cold pressing (respectively b1, b2, b3). That is, the cold pressing elongation (η)η=(b / a-1)*100%.

[0195] 2) First effect

[0196] The first efficiency, that is, the first charge and discharge efficiency, also known as the first coulomb efficiency, is the ratio of the first charge capacity D0 to the first discharge capacity C0 of a secondary battery (specifically a sodium ion battery in the embodiment of the present application) during the first charge and discharge process.

[0197] The specific test method is as follows:

[0198] At 25°C, the sodium ion battery is charged at a constant current rate of 0.2C for 1 hour, and the corresponding capacity is recorded as IGC0; then it is discharged at a rate of 0.1C to 1.5V, and the corresponding capacity is recorded as AGD0; it is allowed to stand for 5 minutes; then the sodium ion battery is charged to 4.2V at a rate of 0.5C, and the corresponding capacity is recorded as AGC0; it is allowed to stand for 5 minutes; then it is discharged at 0.1C to 1.5V, and the corresponding capacity is recorded as AGD1; wherein C0 is ICC0-AGD0+AGC0; D0 is AGD1; the first effect = D0 / C0*100%.

[0199] 3) 45℃ cycle

[0200] At 45°C, the sodium-ion battery was charged to 4.2V at a rate of 0.5C, then charged at a constant voltage until the current was less than 0.05C, and then discharged to 1.5V at a rate of 1C. The cycle test was performed in this full charge and discharge form until the discharge capacity of the lithium-ion battery decayed to 80% of the initial capacity, and the number of cycles at this time was recorded.

[0201] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A pole piece, characterized in that: The pole piece includes a current collector, a conductive buffer layer and an active layer which are stacked in sequence, wherein at least one of the conductive buffer layer and the active layer contains a carbon material, and the carbon material includes one or more of graphite, soft carbon and ethylene.

2. The pole piece according to claim 1, characterized in that: The Dv50 of the carbon material is 0.4 to 1.5 μm; And / or, the Dv90 of the carbon material is 1 to 4 μm.

3. The pole piece according to claim 1 or 2, characterized in that: The Dv50 of the carbon material is 0.7 to 0.9 μm; And / or, the Dv90 of the carbon material is 1 to 3 μm.

4. The pole piece according to any one of claims 1 to 3, characterized in that: The conductive buffer layer includes the carbon material, and the mass content of the carbon material in the conductive buffer layer is greater than or equal to 5% and less than 100%.

5. The pole piece according to claim 4, characterized in that: The mass content of the carbon material in the conductive buffer layer is 14% to 56%.

6. The pole piece according to any one of claims 1 to 5, characterized in that: The active layer contains the carbon material, and the mass content of the carbon material in the active layer is 1% to 5%.

7. The pole piece according to claim 6, characterized in that: The mass content of the carbon material in the active layer is 3% to 5%.

8. The pole piece according to any one of claims 1 to 7, characterized in that: The thickness of the conductive buffer layer is 3-6 μm.

9. The pole piece according to claim 8, characterized in that: The thickness of the conductive buffer layer is 3-4 μm.

10. A method for preparing a pole piece, characterized in that: The method comprises the following steps: preparing a conductive buffer layer on the surface of a current collector; preparing an active layer on the surface of the conductive buffer layer; wherein at least one of the conductive buffer layer and the active layer comprises a carbon material, and the carbon material comprises one or more of graphite, soft carbon and ethylene.

11. The preparation method according to claim 10, characterized in that: The step of preparing the conductive buffer layer includes: providing a primer slurry, and coating the primer slurry on the surface of the current collector.

12. The preparation method according to claim 11, characterized in that: The viscosity of the primer slurry at 25° C. is 100 to 1000 mPa / s.

13. The preparation method according to claim 11 or 12, characterized in that: The viscosity of the primer slurry at 25° C. is 300-600 mPa / s.

14. A battery, characterized in that: The battery comprises the electrode sheet according to any one of claims 1 to 9, or comprises the electrode sheet prepared by the method according to any one of claims 10 to 13.

15. An electrical device, characterized in that: The electrical device comprises the battery according to claim 14.

Citation Information

Patent Citations

  • Silicon-carbon negative pole piece, manufacturing method thereof, lithium ion battery and manufacturing method thereof

    CN102769121A

  • Lithium titanate battery negative pole piece and preparation method thereof

    CN107732147A

  • Lithium ion battery positive plate and preparation method thereof, and lithium ion battery

    CN109037592A

  • Lithium battery pole piece, preparation method thereof and lithium battery

    CN109830689A

  • Electrode pole piece and electrochemical device

    CN110943200A